Computation of a Summation Formula Clung to Recurrence Relation (Global Journal of Science Frontier Research, 2013)
In this paper we have established a summation formula clung to contiguous relation and recurrence relation.
Keywords: gaussian hypergeometric function; contiguous function; recurrence relation of gamma function; bailey summation theorem and legendre duplication formul